Selective Frontoinsular von Economo Neuron and Fork Cell Loss in Early Behavioral Variant Frontotemporal Dementia - Kim, Eun-Joo (Oxford University Press, 2012)
Behavioral variant frontotemporal dementia (bvFTD) erodes complex social–emotional functions as the anterior cingulate cortex (ACC) and frontoinsula (FI) degenerate, but the early vulnerable neuron within these regions has remained uncertain. Previously, we demonstrated selective loss of ACC von Economo neurons (VENs) in bvFTD. Unlike ACC, FI contains a second conspicuous layer 5 neuronal morphotype, the fork cell, which has not been previously examined. Here, we investigated the selectivity, disease-specificity, laterality, timing, and symptom relevance of frontoinsular VEN and fork cell loss in bvFTD. Blinded, unbiased, systematic sampling was used to quantify bilateral FI VENs, fork cells, and neighboring neurons in 7 neurologically unaffected controls (NC), 5 patients with Alzheimer's disease (AD), and 9 patients with bvFTD, including 3 who died of comorbid motor neuron disease during very mild bvFTD. bvFTD showed selective FI VEN and fork cell loss compared with NC and AD, whereas in AD no significant VEN or fork cell loss was detected. Although VEN and fork cell losses in bvFTD were often asymmetric, no group-level hemispheric laterality effects were identified. Right-sided VEN and fork cell losses, however, correlated with each other and with anatomical, functional, and behavioral severity. This work identifies region-specific neuronal targets in early bvFTD.